Revival type : digital typefaces inspired by the past - Shaw, Paul, 1954-; Hoefler, Jonathan (London : Thames & Hudson, 2017)
In this fascinating tour through typographic history, Paul Shaw provides a visually rich exploration of digital type revival. Many typefaces from the pre-digital past have been reinvented for use on computers and mobile devices, while other new font designs are revivals of letterforms, drawn from inscriptions, calligraphic manuals, posters, and book jackets. Revival Type deftly introduces these fonts, many of which are widely used, and engagingly tells their stories. Examples include translations of letterforms not previously used as type, direct revivals of metal and wood typefaces, and looser interpretations of older fonts. Among these are variations on classic designs by John Baskerville, Giambattista Bodoni, William Caslon, Firmin Didot, Claude Garamont, Robert Granjon, and Nicolas Jenson, as well as typefaces inspired by less familiar designers, including Richard Austin, Philippe Grandjean, and Eudald Pradell. Updates and revisions of 20th-century classics such as Palatino, Meridien, DIN, Metro, and Neue Haas Grotesk (Helvetica) are also discussed. Handsomely illustrated with annotated examples, archival material depicting classic designs, and full character sets of modern typefaces, Revival Type is an essential introduction for designers and design enthusiasts into the process of reinterpreting historical type.
Foreword -- Introduction -- Terminology -- Inscriptional letters -- Blackletter -- Venetian oldstyle and aldine types -- French oldstyle types -- Dutch oldstyle types -- Transitional types -- Neoclassical types -- Fat faces -- Slab serifs -- Wood type -- Late Victorian types -- 20th century seriffed types -- Grotesques and gothics -- Geometric sans serifs -- Humanist sans serifs -- Scripts.
Includes bibliographical references (pages 244-245) and index.
Keywords: Graphic design (Typography).; Printing -- Specimens; Technology; Technology; Type and type-founding -- Specimens; Type and type-founding -- Digital techniques; Type and type-founding -- Digital techniques; Type and type-founding.; Type and typefounding -- History; Specimens